Labyrinth: To See vs. to Foresee - Milerius, Nerijus (Problemos, 2000)
The article presents some etudes on the distinction between disengaged, objectifying and engaged, existential thinking. The differences between them are showed through their attitude to the metaphor of the labyrinth. The author overviews some notions of R. Descartes, G.W.R. Hegel, on the one side, and S.Kierkegaard, L. Wittgenstein, on the other. It is argued that the disengaged, objectifying thinking seeks to foresee, to go beyond the labyrinth as the nexus of the one-sided, contingent situations. The engaged thinking, contrary, accepts the labyrinth of the everyday situations. It permanently transgresses the labyrinth only by means of the intensity of the concrete engagement.